Problematika Dan Solusi Pada Pengadaan Tanah Jalur Kereta Api Bandara Yogyakarta Internasional Airport - Deo Enggartiasto; Setiowati Setiowati; Rochmat Martanto (Tunas Agraria, 2021)
The Yogyakarta International Airport Railway Project provides easier access for the public. The implementation of land acquisition for the YIA Airport Railroad has experienced obstacles, namely the length of time providing compensation to people who are entitled to LMAN financing. In addition, there is a problem with the proof of the right to compensation for the land parcels of the 2019 PTSL participants whose certificates were issued after the IPL. This study uses a qualitative method with a descriptive approach, data comes from several parties who are considered important and are directly involved in the land acquisition process. The results showed that the process of paying compensation through LMAN was considered quite long by the community. This is due to the existence of a review and verification process according to separate standard operating procedure outside of Law Number 2 of 2012. Regarding these problems, it is important that land acquisition regulations with LMAN funding be issued. In addition, the delivery of information related to land acquisition to the community is the most important part for the community to cooperate. Proyek Jalur Kereta Api Bandara Yogyakarta International Airport memberikan akses yang lebih mudah bagi masyarakat. Pelaksanaan pengadaan tanah Jalur Kereta Api Bandara YIA mengalami kendala yaitu lamanya pemberian uang ganti rugi terhadap masyarakat yang berhak pada pembiayaan LMAN. Selain itu terdapat permasalahan alas bukti hak untuk ganti rugi pada bidang tanah peserta PTSL 2019 yang sertipikatnya keluar setelah IPL. Penelitian ini menggunakan metode kualitatif dengan pendekatan deskriptif, data berasal dari beberapa pihak yang dianggap penting dan terlibat langsung pada proses pengadaan tanah. Hasil penelitian menunjukkan proses pembayaran uang ganti rugi melalui LMAN dianggap cukup lama oleh masyarakat. Hal ini disebabkan adanya proses review dan verifikasi sesuai SOP tersendiri di luar Undang- Undang Nomor 2 Tahun 2012. Terhadap permasalahan tersebut, penting kiranya diterbitkan peraturan pengadaan tanah dengan pendanaan LMAN. Selain itu penyampaian informasi terkait pengadaan tanah kepada masyarakat menjadi bagian terpenting agar masyarakat kooperatif.Kata Kunci:  Pengadaan Tanah, LMAN, Review, Verifikasi.